Developing scalable woven textile-based scaffolds for tubular tissues with Core–Sheath nanofibre yarns and tuneable weave architectures - Doersam, Anna; Larrea Murillo, Luis; Jones, Celina; Tsigkou, Olga (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionEngineering functional tubular tissues requires scaffolds that replicate the anatomical complexity, mechanical behaviour, and biological microenvironment of native organs.MethodsHere, we present a scalable, automated weaving strategy combining PLA multifilament cores with electrospun PCL nanofibre sheaths to fabricate biomimetic core-sheath yarns. These yarns were woven into tubular scaffolds with tunable architectures, enabling precise control over surface topography, porosity, and mechanical compliance.ResultsWhile microscale cues such as fibre diameter and chemistry are critical, we show that mesoscale weave geometry also modulates cell spatial distribution, orientation, and network formation. Plain weave patterns supported uniform endothelial and smooth muscle cell attachment, viability, and proliferation, while more complex weaves modulated cytoskeletal organisation and multilayer formation. Mechanical characterisation confirmed enhanced strength and elasticity compared to pure nanofibre yarns, yielding more tissue-like mechanical performance.Discussion/ConclusionThis approach overcomes key limitations of traditional electrospun membranes and manual weaving methods by offering reproducibility, structural stability, and design flexibility. Our results demonstrate that controlling yarn morphology and mesoscopic weave architecture can guide cell behaviour and tissue organisation, providing a promising platform for engineering vascular, tracheal, and oesophageal grafts with clinically relevant properties.